Teacher Feedback in Online Education for Trainee Translators - Neunzig, Wilhelm; Tanqueiro, Helena (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe authors present their views on the importance of providing individual, immediate feedback in on-line teaching. This guarantees “teacher-student dialogue”, through which the teacher can provide feedback on student translations, offer prompts and strategies, and correct and support students since they are aware of their individual strengths and weaknesses. The authors have adapted the Proxy program, enabling the teacher to . “spy”. on the student’s computer, and have combined it with the well-known Winpopup application permitting messages to be sent to the students’ computer screen. An empirical experiment is described involving students of German and Portuguese, which provides initial data on the appropriateness of different feedback paradigms for on-line and distance education of trainee translators.